A cidade sitiada - Lispector, Clarice (Rio de Janeiro : Rocco, 1998)
"Revised edition of Lispector's third novel is based on its second edition, the last one reformulated by the author"--Handbook of Latin American Studies, v. 58.
Mode of access: Internet.